Occupational, safety and health issues: Risk management in remote photovoltaic stand-alone system installation / Shahril lrwan Sulaiman and Dayang Nailul Munna Abang Abdullah - Sulaiman, Shahril lrwan; Abang Abdullah, Dayang Nailul Munna (2004)
Photovoltaic industries have begun to secure a positive pace in the local energy market with more photovoltaic (Pv) systems are being installed currently. For stand alone applications, most of the PV systems are installed in remote sites which are almost inaccessible by roads. This can result in risks that are not limited to U1e actual sites. Therefore, there should be an effective risk management process to ensure the safely of workers involved. This paper discusses about the risks associated with PV installation in isolated areas. Identification, analysis and evaluation of these risks are explained in details to confront the safety issues during PV installation.